Application and Theory of Petri Nets and Concurrency: 36th International Conference, PETRI NETS 2015, Brussels, Belgium, June 21-26, 2015, Proceedings - Devillers, R (Springer, 2015)
This book constitutes the proceedings of the 36th International Conference on Application and Theory of Petri Nets and Concurrency, PETRI NETS 2015, held in Brussels, Belgium, in June 2015.